Positive electrode for lithium-ion secondary batteries and lithium-ion secondary batteries
Patent Information
- Application Number
- JP2025062744
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-04
- Publication Date
- 2026-10-16
AI Technical Summary
【0013】 本発明によれば、高温使用時におけるサイクル容量維持率および安全性の低下を抑制することができる。
Smart Images

Figure 2026169069000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a positive electrode for a lithium-ion secondary battery and a lithium-ion secondary battery. [Background technology]
[0002] Lithium-ion secondary batteries offer advantages such as miniaturization, weight reduction, and high capacity due to their high energy density. For example, batteries using high-energy-density active materials such as NCM (Nickel-Cobalt-Manganese Compound), which is mainly composed of nickel, cobalt, and manganese, or layered rock salt compounds represented by lithium cobalt oxide (LCO), as the positive electrode are widely used in applications ranging from small devices such as wearable terminals and power tools to large-scale applications such as automobiles and industrial equipment (see, for example, Patent Document 1). In particular, the use of lithium-ion secondary batteries has increased significantly in large-scale applications, and in recent years, there has been a growing demand for applications used in close proximity to people, such as in automobiles. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2015-103331 [Overview of the Initiative] [Problems that the invention aims to solve]
[0004] Incidentally, layered rock salt type positive electrode active materials such as LCO have low structural stability, especially at high temperatures, and a reduced cycle capacity retention rate when used under high voltage, as lithium ions detach from the interlayers. Furthermore, when abnormal charging occurs, the transition metals constituting the positive electrode active material may dissolve into the electrolyte and precipitate on the negative electrode, generating lithium dendrites and potentially causing an internal short circuit, thus reducing safety.
[0005] The present invention has been made in view of the above circumstances, and an object thereof is to provide a positive electrode for lithium ion secondary batteries and a lithium ion secondary battery that can suppress the decrease in cycle capacity retention rate and safety during high-temperature use. [Means for Solving the Problems]
[0006] As a result of extensive and intensive studies to solve the above problems, in the positive electrode, the peak integrated intensity I of the diffraction peak showing the (006) plane within the range of 2θ=38°±5° obtained by X-ray diffraction measurement (XRD) (006) and the peak integrated intensity I of the diffraction peak showing the (104) plane within the range of 2θ=45°±5° obtained by X-ray diffraction measurement (XRD) (104) the integrated intensity ratio I (006) / I (104) satisfies I (006) / I (104) >0.3, the inventors have found that the decrease in cycle capacity retention rate and safety during high-temperature use can be suppressed, and have completed the present invention.
[0007] In a first aspect, the positive electrode for lithium ion secondary batteries according to the present invention is a positive electrode for non-aqueous electrolyte secondary batteries including a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector, wherein the positive electrode mixture layer contains a lithium transition metal oxide having a layered rock salt type crystal structure, and the peak integrated intensity I of the diffraction peak showing the (006) plane within the range of 2θ=38°±5° obtained by X-ray diffraction measurement (XRD) (006) and the peak integrated intensity I of the diffraction peak showing the (104) plane within the range of 2θ=45°±5° obtained by X-ray diffraction measurement (XRD) (104) the integrated intensity ratio I (006) / I (104) satisfies I (006) / I (104) >0.3.
[0008] Further, in a second aspect, in addition to the first aspect, the positive electrode for lithium ion secondary batteries according to the present invention is characterized in that the electrode density is 3.3 g / cc or more and 3.7 g / cc or less.
[0009] Furthermore, as a third aspect, the positive electrode for the lithium-ion secondary battery according to the present invention, in addition to the first or second aspect, has a peak integral intensity I of the diffraction peak showing the (003) plane within the range of 2θ = 19° ± 5° obtained in X-ray diffraction measurement (XRD). (003) And the aforementioned peak integral intensity I (104) The integral intensity ratio I (003) / I (104) However, I (003) / I (104) It is characterized by satisfying the condition >10.
[0010] Furthermore, as a fourth aspect, the positive electrode for a lithium-ion secondary battery according to the present invention is characterized in that, in addition to the first to third aspects, the lithium transition metal oxide is lithium cobalt oxide.
[0011] Furthermore, the positive electrode for a lithium-ion secondary battery according to the present invention is characterized in that, in addition to the first to fourth aspects, the average particle size of the lithium transition metal oxide is 5 μm or more and 10 μm or less.
[0012] Furthermore, the lithium-ion secondary battery according to the present invention is characterized in that, as a sixth aspect, it comprises a positive electrode for a lithium-ion secondary battery relating to any one of the first to fifth aspects, a negative electrode capable of intercalating and releasing lithium ions, and a non-aqueous electrolyte. [Effects of the Invention]
[0013] According to the present invention, it is possible to suppress the decrease in cycle capacity maintenance rate and safety when used at high temperatures. [Brief explanation of the drawing]
[0014] [Figure 1] Figure 1 is a perspective view illustrating the configuration of a lithium-ion secondary battery according to Embodiment 1 of the present invention. [Figure 2] Figure 2 is a cross-sectional view along line AA shown in Figure 1. [Figure 3] Figure 3 is a diagram illustrating the lattice planes of the crystal structure. [Figure 4] Figure 4 is an exploded perspective view illustrating the configuration of a non-aqueous electrolyte secondary battery equipped with a positive electrode for a non-aqueous electrolyte secondary battery according to Embodiment 2 of the present invention. [Modes for carrying out the invention]
[0015] The embodiments of the present invention will be described below, but the present invention is not limited to the following description. Furthermore, various modifications or improvements can be made to these embodiments, and such modified or improved forms may also be included in the present invention. In the following, an example configuration of a stacked lithium-ion secondary battery is shown as an example of an embodiment. However, the shape of the lithium-ion secondary battery in the present invention is not particularly limited and may be flat, cylindrical, prismatic, or coin-shaped. Furthermore, the casing of the lithium-ion secondary battery is not particularly limited and known materials such as laminate film, aluminum, aluminum alloy, and stainless steel can be used.
[0016] (Embodiment 1) Figure 1 is a perspective view illustrating the configuration of a lithium-ion secondary battery according to Embodiment 1 of the present invention. Figure 2 is a cross-sectional view taken along line AA shown in Figure 1.
[0017] The lithium-ion secondary battery 1 is a stacked lithium-ion secondary battery comprising an outer casing 2 formed in a bag shape by overlapping two laminate films so that the heat-sealable resin layers face each other and heat-sealing the outer edges.
[0018] The outer casing 2 is formed into a bag shape by overlapping two laminate films so that the heat-sealable resin layers face each other, and then heat-sealing the outer edges. The electrode group 3 and the non-aqueous electrolyte are housed inside the outer casing 2. The electrode group 3 is inserted through the opening of the outer casing 2, and the opening of the outer casing 2 is heat-sealed to enclose the electrode group 3 in an airtight manner.
[0019] As the laminate film, a composite film having a metal layer with a heat-sealable resin layer is preferably used. The metal layer is not particularly limited as long as it prevents moisture from entering from the outside while improving the overall strength of the sheet. For example, aluminum foil, stainless steel foil, etc., can be used as the metal layer. Furthermore, while the heat-sealable resin layer is not particularly limited, polyethylene and polypropylene are preferably used from the viewpoint of a heat-sealable temperature range and barrier properties against non-aqueous electrolytes. Here, to protect the metal layer, a protective layer may be provided on the side opposite to the heat-fusible resin layer. The protective layer is not particularly limited, but nylon, PET, etc., are preferably used. In addition, an adhesive layer may be provided between the metal layer and the heat-fusible resin layer to improve their adhesion.
[0020] As shown in Figure 2, the electrode group 3 has a structure in which a positive electrode 4, a negative electrode 5, and a separator 6 interposed between the positive electrode 4 and the negative electrode 5 are stacked as a set, with the negative electrode 5 located in the outermost layer, and multiple such sets are stacked.
[0021] (positive electrode) The positive electrode 4 consists of a positive electrode current collector 42 and a positive electrode composite material layer 41 formed on both or one side of the positive electrode current collector 42. The positive electrode 4 is plate-shaped.
[0022] The positive electrode composite layer 41 includes a positive electrode active material, a conductive agent, and a binder.
[0023] <Cathode active material> As the positive electrode active material, a lithium transition metal oxide having a layered rock-salt type crystal structure can be used. The lithium transition metal oxide having a layered rock-salt type crystal structure contains lithium, a transition metal, and oxygen. For example, a composite oxide represented by LiMO2 (M is a transition metal) can be used. Here, the transition metal M is preferably at least one selected from, for example, Co, Ni, and Mn. Specifically, lithium cobalt oxide (LiCoO2: LCO), lithium nickel oxide (LiNiO2), lithium manganate (LiMnO2), lithium nickel cobalt manganate (LiCo x Ni y Mn 1-x-y O2 (0<x+y<1, 0<x, 0<y)) and the like. In particular, LCO is suitable as the lithium transition metal oxide because it has advantages such as large capacity, stability in the atmosphere, and relatively high thermal stability.
[0024] Moreover, the average particle diameter of the lithium transition metal oxide having a layered rock-salt type crystal structure is preferably 5 μm or more and 10 μm or less. When the average particle diameter is less than 5 μm, the specific surface area of the active material increases, and the conductive paths are insufficient relative to the specific surface area, which may increase the reaction resistance. When the average particle diameter is larger than 10 μm, there is a possibility that the diffusivity of lithium ions in the active material particles decreases, and that the specific surface area of the active material decreases to reduce the reaction area, which may increase the reaction resistance. The average particle diameter is the value of the median diameter (D50) measured by the laser diffraction / scattering method described in JIS Z8825:2013. For the measurement, a laser diffraction particle size distribution analyzer SALD-2300 (manufactured by Shimadzu Corporation) can be used.
[0025] Whether LCO is contained as the positive electrode active material can be confirmed by observation using a Scanning Electron Microscope (SEM) and Energy Dispersive X-ray Spectroscopy (EDS), and by X-ray diffraction (XRD).
[0026] <Conductive agent> The conductive agent is not particularly limited, and known or commercially available ones can be used. Examples of conductive agents include carbon black such as acetylene black and Ketjen black, carbon nanotubes, carbon fibers, activated carbon, and conductive carbon such as graphite. The conductive agent can be used individually or as a mixture of several of these.
[0027] <Binding agent> The binder is not particularly limited, and known or commercially available binders can be used. Examples include fluororesins such as polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE), polyvinylpyrrolidone (PVP), polyvinyl chloride (PVC), polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, styrene-butadiene rubber (SBR), acrylic resin, polyvinyl alcohol (PVA), or carboxymethylcellulose (CMC). The binder can be used individually, or as a mixture or copolymer of two or more of these substances.
[0028] <Dispersant> Dispersants are not always necessary, but they can be added if you want to further disperse conductive agents or other materials. Typical dispersants include polyvinylpyrrolidone (PVP).
[0029] <Positive electrode current collector> The positive electrode current collector 42 is not particularly limited, and known or commercially available ones can be used. Examples of the positive electrode current collector 42 include rolled foil made of aluminum, aluminum alloy, copper, nickel, or stainless steel, and porous metals such as porous aluminum. Among these candidates for the positive electrode current collector, aluminum or aluminum alloy is preferred because it has high electrical conductivity, excellent corrosion resistance in the electrolyte, and is a lightweight metal.
[0030] In this embodiment 1, the positive electrode 4 is the peak integral intensity I of the diffraction peak that shows the (006) plane within the range of 2θ = 38° ± 5° in X-ray diffraction measurement (XRD). (006) And the peak integral intensity I of the diffraction peak showing the (104) plane within the range of 2θ = 45° ± 5° (104) The integral intensity ratio I (006) / I (104) is greater than 0.3 (I (006) / I (104) It is characterized by >0.3).
[0031] Figure 3 is a diagram illustrating the lattice planes of the crystal structure. Lithium atom E Li Cobalt atom E Co and oxygen atom E O In an LCO composed of the above, the (006) plane is composed of lithium ions (Li + This is a diffraction plane that is parallel to the (003) plane, which is an ion diffusion pathway, and shares the same cobalt atoms as the (104) plane, which forms the framework of the layered structure. Integrated intensity ratio I (006) / I (104) A large integral intensity ratio indicates that the layer framework is oriented along the c-axis direction, and the crystallinity of the (006) plane is high. As a result, it is thought that the breakdown of the layer structure due to cation mixing is more easily suppressed. This improves the cycle performance under high voltage and high temperature conditions, suppresses the elution of transition metal ions during abnormal charging, and enhances safety. Specifically, the integral intensity ratio I (006) / I (104) If it is greater than 0.3, the structure is robust, and lithium ions (Li + It is thought that the insertion and removal of ) can be performed efficiently.
[0032] Furthermore, the peak integral intensity I of the diffraction peaks showing the (003) plane within the range of 2θ = 19° ± 5°, obtained in X-ray diffraction measurements (XRD) (003) And the peak integral intensity I of the diffraction peak showing the (104) plane (104) The integral intensity ratio I (003) / I (104) is greater than 10 (I (003) / I (104)>10) is preferable. Integrated intensity ratio I (003) / I (104) A larger value indicates higher crystallinity, which in turn makes it easier to suppress the breakdown of the layer structure due to cation mixing. Therefore, the integrated intensity ratio I (003) / I (104) The integral intensity ratio I is greater than 10. (006) / I (104) When the integral intensity ratio is greater than 0.3, the crystallinity of the (003) and (006) planes is high, effectively suppressing cation mixing, and the framework that maintains the layer structure becomes more robust, which can improve cycle performance, especially under high temperature and high voltage operation. (003) / I (104) When the value is 10 or less, the crystallinity of the (003) plane is insufficient, which makes cation mixing more likely. In addition, the exposure of the pathways through which lithium ions are inserted and removed from the electrode surface increases, which is thought to lead to a decrease in cycle performance due to electrolyte decomposition and a higher likelihood of transition metal elution.
[0033] Here, the integrated intensity ratio I (006) / I (104) This changes from a powder state to an electrode state, and varies depending on the mixing method and pressing strength (electrode density). Specifically, the integrated intensity ratio I (006) / I (104) This has a positive correlation with the electrode density and can be adjusted by the electrode density during the activation process. In this case, it is preferable to set the electrode density to 3.3 g / cc or more and 3.7 g / cc or less. If the electrode density is less than 3.3 g / cc, the press strength is insufficient, resulting in uneven orientation of the active material, and the effects of the present invention cannot be fully obtained. On the other hand, if the electrode density is greater than 3.7 g / cc, the orientation of the active material becomes uniform, and the integral intensity ratio I (006) / I (104) Even if the value exceeds 0.3, cracks and fissures may occur in the active material particles, potentially leading to a decrease in cycle capacity retention and increased leaching of transition metals during high-temperature use.
[0034] [Electrode fabrication method] The positive electrode can be manufactured, for example, by the following method. First, the positive electrode active material, conductive agent, binder, and dispersant mentioned above are dispersed in a solvent to prepare a positive electrode slurry. A thickening agent may be further added to the positive electrode slurry. Subsequently, the positive electrode slurry is applied to one or both sides of the positive electrode current collector, dried to form a positive electrode composite layer, and then rolled to produce a plate-shaped positive electrode.
[0035] <Solvent> The solvent used in preparing the positive electrode slurry is not particularly limited, and known or commercially available solvents can be used. Examples of solvents include N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMA), and water. When polyvinylidene fluoride (PVDF) is used as the binder, it is preferable to use N-methyl-2-pyrrolidone (NMP) as the solvent. When styrene-butadiene rubber (SBR), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), or carboxymethylcellulose (CMC) is used as the binder, it is preferable to use water as the solvent. Furthermore, it is preferable to use polyvinylpyrrolidone (PVP) as the dispersant.
[0036] Furthermore, the positive electrode 4 has a positive electrode lead 43 extending from the positive electrode composite layer 41 by the positive electrode current collector 42. The positive electrode lead 43 extends from the right side, for example, in Figure 2. Each positive electrode lead 43 is bundled at its tip within the outer casing 2 and joined to each other by ultrasonic welding, resistance welding, or the like. The positive electrode terminal 7 has one end joined to the joint of the positive electrode lead 43, and the other end extends to the outside through the sealing portion of the outer casing 2.
[0037] (Negative electrode) The negative electrode 5 is composed of a negative electrode current collector 52 and a negative electrode composite layer 51 containing a negative electrode active material or metallic lithium (not shown) formed on one or both sides of the negative electrode current collector 52.
[0038] The negative electrode composite layer 51 is, for example, metallic lithium, lithium-titanium niobium alloy, or graphite, amorphous carbon, or transition metal composite oxide (e.g., Li4Ti5O 12 The active material includes at least one selected from lithium-capable alloys (such as TiNb2O7), or silicon. Among these, graphite is preferred because it has an operating potential very close to that of metallic lithium, allows for charging and discharging at high operating voltages, and has excellent cycle characteristics. Graphite may also be used in combination with other negative electrode active materials. The negative electrode composite layer 51 also contains a binder. The negative electrode composite layer 51 may also contain a conductive agent. The binder and conductive agent can be materials equivalent to those used in the positive electrode 4.
[0039] The negative electrode current collector 52 is not particularly limited, but it is preferable to use a metal. Suitable metals include, for example, aluminum foil and copper, and porous aluminum current collectors may also be used depending on the application. Among these, copper is preferred from the viewpoint of electronic conductivity and battery operating potential.
[0040] Furthermore, the negative electrode 5 has, for example, a negative electrode current collector 52 with a negative electrode lead 53 extending from the negative electrode composite layer 51. In Figure 2, for example, the negative electrode lead 53 extends from the left side. Each negative electrode lead 53 is bundled at its tip within the outer casing 2 and joined to one another. The negative electrode terminal 8 has one end joined to the joint of the negative electrode lead 53, and the other end extends to the outside through the sealing portion of the outer casing 2.
[0041] (Non-aqueous electrolyte) The non-aqueous electrolyte contains a non-aqueous solvent in which a lithium salt is dissolved. The lithium salt is not particularly limited, but examples include one or more mixtures selected from the group consisting of LiBF4, LiPF6, Li(FSO2)2N, Li(CF3SO2)2N, and LiPO2F2. The non-aqueous solvent is not particularly limited, but examples include one or more mixed solvents selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), methyl propionate, ethyl propionate, propyl propionate, methyl acetate, methyl formate, methyl butyrate, dioxolane, 2-methyltetrahydrofuran, tetrahydrofuran, dimethoxyethane, γ-butyrolactone, acetonitrile, and benzonitrile. DMC, DEC, DPC, EMC, EC, and PC are particularly preferred. In particular, it is preferable to include EC that enables good film formation on the negative electrode active material.
[0042] Furthermore, the non-aqueous electrolyte may contain additives. Possible additives include vinylene carbonate (VC), fluoroethylene carbonate, allylsuccinic anhydride (ASAh), 1,3-dioxane (DO), lithium bisoxalate borate, lithium tetrafluoroborate (LiBF4), propanesultone, succinonitrile, acetonitrile, 1,3,6-hexanetricarbonitride, and 1,2,3-tris(2-cyanoethoxy)propane, which can be used individually or in combination of two or more of these.
[0043] (Separator) The separator 6 is not particularly limited, and known or commercially available separators can be used. For example, the separator 6 can be a sheet made of a microporous membrane composed of polyethylene resin, polyolefin resin such as polypropylene resin, polyimide resin, or polytetrafluoroethylene (PTFE) resin. The microporous membrane or nonwoven fabric may be a single layer or a multilayer structure. Furthermore, a coating layer may be applied to one or both sides of the separator. The material of the coating layer is not particularly limited, but inorganic materials such as alumina or boehmite can be used.
[0044] The shape of the electrode elements is not particularly limited; the positive electrode, negative electrode, and separator may be wound together, stacked in a single-sheet configuration, or folded in a zigzag pattern.
[0045] It is preferable that such lithium-ion secondary batteries undergo pretreatment, such as initial charging and gas evacuation, before being used as batteries. For initial charging, for example, after injecting a non-aqueous electrolyte, constant current charging is performed at a small current value until the rated capacity reaches 10%. After such initial charging, gas generated inside the casing during the initial charging is evacuated. Gas evacuation is performed, for example, by placing the casing in a reduced pressure chamber with a part of the sealing portion open. Gas evacuation can be accelerated, for example, by pressing the casing from the outside during gas evacuation.
[0046] The presence of an active material capable of intercalating and deintercalating lithium in the electrode's constituent materials can be confirmed by cyclic voltammetry. By preparing the target electrode as the working electrode, using lithium metal as the counter electrode, and constructing a coin cell with separator 6 in between, and performing several cycles of cyclic voltammetry measurements using an electrochemical test apparatus, it is possible to confirm whether lithium is capable of intercalating and deintercalating lithium by observing the reversible occurrence of redox reaction peaks.
[0047] Furthermore, the capacity of the lithium-ion secondary battery 1 can be confirmed by charge-discharge testing. Using the upper and lower voltage limits specified by the manufacturer, charging is performed at 0.5 ItA, with CV switching at the upper voltage limit and a 0.05 ItA cutoff. Discharging is performed at 0.2 ItA, with a cutoff at the lower voltage limit. The battery capacity can then be confirmed from the discharge capacity.
[0048] In the embodiment 1 described above, the positive electrode 4 is the peak integral intensity I of the diffraction peak showing the (006) plane in X-ray diffraction measurement (XRD). (006) And the peak integral intensity I of the diffraction peak showing the (104) plane (104) The integral intensity ratio I (006) / I (104) The value was made greater than 0.3. According to this embodiment 1, lithium ions (Li) are directed to the (104) plane, which is part of the framework of the layered rock salt structure. + By increasing the strength of the (006) plane, which is parallel to the (003) plane that serves as a diffusion pathway and has cobalt atoms common to the (104) plane, the active material framework can be made into a robust and stable electrode. As a result, the decrease in cycle capacity retention rate during high-temperature use is suppressed, and the elution of transition metal ions during abnormal charging is suppressed, thereby improving safety.
[0049] (Embodiment 2) Figure 4 is an exploded perspective view illustrating the configuration of a non-aqueous electrolyte secondary battery equipped with a positive electrode for a non-aqueous electrolyte secondary battery according to Embodiment 2 of the present invention. The lithium-ion secondary battery 1A comprises a case 110, a leaf spring 111, a positive electrode current collector 112, a positive electrode composite layer 113, a separator 114, a negative electrode 115, a gasket 116, and a cap 117. The positive electrode 118 is formed by the positive electrode current collector 112 and the positive electrode composite layer 113.
[0050] In lithium-ion secondary battery 1A, the case 110 and cap 117 are fixed together by crimping or the like, and the inside is filled with a non-aqueous electrolyte. In lithium-ion secondary battery 1A, the case 110, gasket 116, and cap 117 seal the battery in a liquid-tight manner. In addition, the positive electrode current collector 112, positive electrode composite layer 113, separator 114, and negative electrode 115 are biased toward the cap 117 by a leaf spring 111. This maintains a state in which each component is in close contact with the others.
[0051] The positive electrode current collector 112 is constructed using the same material as the positive electrode current collector 42. The positive electrode composite layer 113 has the same configuration as the positive electrode composite layer 41.
[0052] The separator 114 is provided between the positive electrode and the negative electrode 115 and has a porous, disc-like shape. The separator 114 has the same configuration as the separator 6.
[0053] The non-aqueous electrolyte can be the non-aqueous electrolyte of Embodiment 1.
[0054] The negative electrode 115 has the same configuration as the negative electrode 5.
[0055] In this second embodiment, the positive electrode 118 of the lithium-ion secondary battery 1A exhibits a peak integral intensity I of the diffraction peak showing the (006) plane in X-ray diffraction measurement (XRD). (006) And the peak integral intensity I of the diffraction peak showing the (104) plane (104) The integral intensity ratio I (006) / I (104) The value was made greater than 0.3. According to this embodiment 2, similar to embodiment 1, lithium ions (Li) are applied to the (104) plane, which is part of the framework of the layered rock salt structure. + By increasing the strength of the (006) plane, which is parallel to the (003) plane that serves as a diffusion pathway and has cobalt atoms common to the (104) plane, the active material framework can be made into a robust and stable electrode. As a result, the decrease in cycle capacity retention rate during high-temperature use is suppressed, and the elution of transition metal ions during abnormal charging is suppressed, thereby improving safety. [Examples]
[0056] The present invention will be described in more detail below with reference to examples, but the present invention is not limited in any way by the following examples.
[0057] (Example 1) <Method for manufacturing the positive electrode> A cathode active material slurry was prepared by mixing lithium cobalt oxide (LCO) with an average particle size (active material particle size) of 6.9 μm as the cathode active material, acetylene black (AB) and conductive carbon or carbon nanotubes as conductive agents, and N-methyl 2-pyrrolidone (NMP) as a binder and viscosity adjusting solvent in appropriate amounts.
[0058] The obtained positive electrode active material slurry was applied to a positive electrode current collector and dried to form a positive electrode composite layer, thereby producing a positive electrode.
[0059] <Method for fabricating the negative electrode> (Negative electrode 1) A 0.5 mm thick metallic lithium foil was used as the negative electrode active material, and negative electrode 1 was fabricated by punching out the metallic lithium foil using a φ16 mm punching machine. (Negative electrode 2) A negative electrode active material slurry was prepared by mixing appropriate amounts of graphite as the negative electrode active material, sodium carboxymethylcellulose as a thickener, styrene-butadiene rubber as a binder, and deionized water as a viscosity adjusting solvent. The obtained negative electrode active material slurry was applied to the negative electrode current collector and dried to form a negative electrode composite layer, thereby fabricating negative electrode 2. The gap setting of the tabletop roll press was set to an arbitrary value, and negative electrode 2 was pressed to achieve the desired electrode density. The pressed electrode was punched out using a φ15.0 mm punch, and the electrode density was calculated by measuring the thickness and weight of the punched electrode including the current collector. The electrode density of negative electrode 2 was determined to be 1.6 g / cc.
[0060] <Preparation of non-aqueous electrolyte> A non-aqueous electrolyte was used, prepared by dissolving 1.3 mol / L of LiPF6 as a lithium salt and 1.0% by weight of vinylene carbonate as an additive in a mixed solvent of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a volume ratio of 2:5:3.
[0061] <Manufacturing of lithium-ion secondary batteries> The fabricated positive electrode was pressed using a tabletop roll press to achieve a predetermined electrode density. The pressed electrode was then punched out in a circular shape and vacuum-dried together with the coin cell components at 60°C for 12 hours. The materials were placed in a glove box filled with inert gas, and a coin cell consisting of the fabricated positive electrode, negative electrode 1, separator, and electrolyte was constructed as a test lithium-ion secondary battery.
[0062] <Measurement of average particle size> The average particle size of the positive electrode active material was determined using the particle size (D50) value, which represents the relative particle amount at 50%, as measured by the laser diffraction / scattering method described in JIS standard Z8825:2013. A laser diffraction particle size distribution analyzer SALD-2300 (manufactured by Shimadzu Corporation) was used for the measurement.
[0063] <Measurement of electrode density> The gap setting of the tabletop roll press was set to an arbitrary value, and the electrodes were pressed to achieve the desired electrode density. The pressed electrodes were punched out using a φ13.5 mm puncher, and the electrode density was calculated by measuring the thickness and weight of the punched-out electrodes, including the current collector. It was assumed that the density of the current collector was constant, and was set to 2.7 g / cc. When measuring the electrode density after removing the electrodes from the cell after testing, the removed electrodes were washed with an electrolyte solvent (e.g., DMC), dried, punched out using a φ13.5 mm puncher, and the density was calculated by measuring the thickness and weight of the punched-out electrodes. At this time, the state of charge (SOC) of the cell was set to 0%.
[0064] <Integrated intensity ratio> For the positive electrode active material, the peak integral intensity I of the diffraction peak showing the (006) plane within the range of 2θ = 38° ± 5°, obtained by X-ray diffraction measurement (XRD) (006) And the peak integral intensity I of the diffraction peak showing the (104) plane within the range of 2θ = 45° ± 5° (104) The integral intensity ratio I is measured and measured. (006) / I (104) They sought it. Furthermore, the peak integral intensity I of the diffraction peak showing the (003) plane within the range of 2θ = 19° ± 5° (003) Measure the peak integrated intensity I (003) and peak integral intensity I (104) The integral intensity ratio I (003) / I (104) They sought it.
[0065] <Capacity retention rate after 20 cycles in a 45°C cycle test> A lithium-ion secondary battery fabricated using negative electrode 1 was evaluated by a 45°C cycle test. The fabricated lithium-ion secondary battery was activated by performing two cycles of CC-CV charging with an upper voltage limit of 4.55V, 0.1C, and cutoff current of 0.05C, and CC discharge with a lower voltage limit of 2.5V and 0.1C, under a 25°C environment. Subsequently, the lithium-ion secondary battery was exposed to a 45°C environment for 4 hours, and 20 cycles of CC-CV charging with an upper voltage limit of 4.55V, 1.0C, and cutoff current of 0.1C, and CC discharge with a lower voltage limit of 2.5V and 1.0C were repeated. The discharge capacity after the 20th charge-discharge cycle under a 45°C environment was defined as the capacity retention rate (%), assuming the discharge capacity after the first charge-discharge cycle under a 45°C environment is 100%. For the 20th cycle, the volume retention rate was judged as follows: 80% or higher was considered a pass (○), and less than 80% was considered a fail (×).
[0066] <Current rise time during continuous charging> The current rise time was measured during continuous charging in a high-temperature (50°C) environment. A lithium-ion secondary battery fabricated using negative electrode 1 was activated by performing two cycles of CC-CV charging at a maximum voltage of 4.55V, 0.1C, and cutoff current of 0.05C, and CC discharge at a minimum voltage of 2.5V and 0.1C, in a 25°C environment. After CC-CV charging of this lithium-ion secondary battery at a maximum voltage of 4.55V, 0.1C, and cutoff current of 0.05C in a 25°C environment, it was exposed to a 50°C environment for 1 hour, and then constant voltage charging was performed at a maximum voltage of 4.60V without specifying a cutoff current. The time change of the current was monitored, and the time when the current exceeded 0.03C was defined as the current rise time. The current rise time was judged as follows: 30 hours or more was considered a pass (○), and less than 30 hours was considered a fail (×).
[0067] <Disassembly and inspection of a battery after 30 hours of continuous charging> The lithium-ion batteries were subjected to 30 hours of continuous charging in a high-temperature (50°C) environment, and the presence or absence of lithium metal deposition on the negative electrode was confirmed by disassembling and examining the fabricated lithium-ion batteries. A lithium-ion secondary battery fabricated using negative electrode 2 was activated by performing one cycle of CC-CV charging at a maximum voltage of 4.4V, 0.1C, and cutoff current of 0.1C in a 25°C environment, followed by CC discharge at a minimum voltage of 2.5V and 0.1C. This lithium-ion secondary battery was then CC-CV charged at a maximum voltage of 4.55V, 0.1C, and cutoff current of 0.05C in a 25°C environment, exposed to a 50°C environment for 1 hour, and then subjected to constant voltage charging at a maximum voltage of 4.6V for 30 hours. After continuous charging, the lithium-ion battery was exposed to a 25°C environment for 1 hour, and the SOC was adjusted to 0% by CC discharge at a minimum voltage of 2.5V and 0.2C. The lithium-ion battery was placed in a glove box filled with inert gas, and the battery was disassembled to observe the negative electrode. The judgment was based on whether there was no metallic luster on the negative electrode that could be attributed to lithium metal deposition (pass, ○), and whether there was metallic luster (fail, ×).
[0068] <Overall Rating> The comprehensive evaluation regarding the 20th cycle capacity retention rate, current rise time, and lithium metal deposition was defined as Pass (○) when all items were acceptable, and Fail (×) when even one item was unacceptable.
[0069] The configuration and test results of the battery in Example 1 are shown in Table 1. In Example 1, the integrated intensity ratio I (006) / I (104) was 0.489, and the integrated intensity ratio I (003) / I (104) was 20.9. [Table 1]
[0070] (Example 2) In Example 2, the same configuration and experimental method as in Example 1 were used, except that the active material particle size of LCO was changed to 7.3 μm. In Example 2, the integrated intensity ratio I (006) / I (104) was 0.376, and the integrated intensity ratio I (003) / I (104) was 12.4. The configuration and test results of the battery in Example 2 are shown in Table 1.
[0071] (Example 3) In Example 3, the same configuration and experimental method as in Example 1 were used, except that the active material particle size of LCO was changed to 9.2 μm. In Example 2, the integrated intensity ratio I (006) / I (104) was 0.353, and the integrated intensity ratio I (003) / I (104) was 13.5. The configuration and test results of the battery in Example 3 are shown in Table 1.
[0072] (Example 4) In Example 4, the same configuration and experimental method as in Example 1 were used, except that the electrode density of the positive electrode was changed to 3.6 g / cc. In Example 3, the integrated intensity ratio I (006) / I (104) was 0.745, and the integrated intensity ratio I (003) / I (104)was 19.3. The configuration of the battery in Example 4 and the test results are shown in Table 1.
[0073] (Example 5) In Example 5, the same configuration and experimental method as in Example 1 were used, except that the electrode density of the positive electrode was changed to 3.0 g / cc. In Example 5, the integrated intensity ratio I (006) / I (104) was 0.458, and the integrated intensity ratio I (003) / I (104) was 12.2. The configuration of the battery in Example 5 and the test results are shown in Table 1.
[0074] (Example 6) In Example 6, the same configuration and experimental method as in Example 1 were used, except that the electrode density of the positive electrode was changed to 3.3 g / cc. In Example 6, the integrated intensity ratio I (006) / I (104) was 0.581, and the integrated intensity ratio I (003) / I (104) was 15.8. The configuration of the battery in Example 6 and the test results are shown in Table 1.
[0075] (Example 7) In Example 7, the same configuration and experimental method as in Example 1 were used, except that the electrode density of the positive electrode was changed to 3.4 g / cc. In Example 7, the integrated intensity ratio I (006) / I (104) was 0.531, and the integrated intensity ratio I (003) / I (104) was 9.6. The configuration of the battery in Example 7 and the test results are shown in Table 1.
[0076] (Example 8) In Example 8, the same configuration and experimental method as in Example 1 were used, except that the active material particle size of LCO was changed to 15.3 μm. In Example 8, the integrated intensity ratio I (006) / I (104) was 0.670, and the integrated intensity ratio I (003) / I (104) was 17.5. The configuration of the battery in Example 8 and the test results are shown in Table 1.
[0077] (Comparative Example 1) In Comparative Example 1, the same configuration and experimental method as in Example 1 were used, except that the active material particle size of LCO was changed to 8.3 μm. In Comparative Example 1, the integrated intensity ratio I (006) / I (104) is 0.265, integrated intensity ratio I (003) / I (104) The value was 6.8. The battery configuration and test results for Comparative Example 1 are shown in Table 1.
[0078] (Comparative Example 2) In Comparative Example 2, the same configuration and experimental method as in Example 1 were used, except that the active material particle size of the LCO was changed to 6.7 μm. In Comparative Example 2, the integrated intensity ratio I (006) / I (104) is 0.227, integrated intensity ratio I (003) / I (104) The value was 5.5. The battery configuration and test results for Comparative Example 2 are shown in Table 1.
[0079] (Comparative Example 3) In Comparative Example 3, the same configuration and experimental method as in Example 1 were used, except that the electrode density of the positive electrode was changed to 2.7 g / cc. In Comparative Example 3, the integrated intensity ratio I (006) / I (104) is 0.290, integrated intensity ratio I (003) / I (104) The value was 10.1. The battery configuration and test results for Comparative Example 3 are shown in Table 1.
[0080] From Table 1, the integrated intensity ratio I (006) / I (104) In Examples 1-8, where the integral intensity ratio was greater than 0.3, both the capacity retention rate at 20 cycles in the 45°C cycle test and the current rise time during continuous charging showed good characteristics, and no lithium metal deposition was observed on the negative electrode after the continuous charging test. Furthermore, the integral intensity ratio I (003) / I (104) In Examples 1-6 and 8, where the integral intensity ratio was greater than 10, a higher capacity retention rate and extended current rise time during continuous charging were observed compared to Example 7. (006) / I (104)In comparative examples 1-3, where the integral intensity ratio was less than 0.3, at least one of the following failed: the capacity retention rate after 20 cycles in the 45°C cycle test, the current rise time during continuous charging, or the deposition of lithium metal on the negative electrode after the continuous charging test. As a result, the integral intensity ratio I (006) / I (104) If the value is greater than 0.3, both the capacity retention rate at 20 cycles in the 45°C cycle test and the current rise time during continuous charging show good characteristics, indicating that lithium metal deposition is suppressed and safety is improved.
[0081] The lithium-ion secondary battery of the present invention can be applied to a variety of applications requiring rapid charging and discharging and high capacity, such as power tools, drones, robots, and electric motorcycles. [Explanation of symbols]
[0082] 1. 1A Lithium-ion rechargeable battery 2. Exterior 3 electrode groups 4, 118 positive electrode 5, 115 negative electrode 6, 114 Separator 7 Positive terminal 8 Negative terminal 41, 113 Positive electrode composite layer 42, 112 Positive electrode current collector 51 Negative electrode composite layer 52 Negative electrode current collector 110 cases 111 Leaf spring 116 Gasket 117 Cap
Claims
1. A positive electrode for a non-aqueous electrolyte secondary battery, comprising a positive electrode current collector and a positive electrode composite layer formed on the surface of the positive electrode current collector, The positive electrode composite layer contains a lithium transition metal oxide having a layered rock salt-type crystalline structure. The peak integrated intensity I of the diffraction peak showing the (006) plane within the range of 2θ = 38° ± 5°, obtained in X-ray diffraction (XRD) measurements. (006) And the peak integrated intensity I of the diffraction peak showing the (104) plane within the range of 2θ = 45° ± 5° (104) The integral intensity ratio I (006) / I (104) However, I (006) / I (104) > Satisfying 0.3 A positive electrode for lithium-ion secondary batteries characterized by the following features.
2. The electrode density is 3.3 g / cc or more and 3.7 g / cc or less. The positive electrode for a lithium-ion secondary battery according to feature 1.
3. Peak integrated intensity I of the diffraction peak indicating the (003) plane within the range of 2θ = 19° ± 5°, which is obtained in X-ray diffraction measurement (XRD) (003) and the aforementioned peak integrated intensity I (104) the integrated intensity ratio I of (003) / I (104) satisfies I (003) / I (104) >10 The positive electrode for a lithium-ion secondary battery according to feature 1.
4. The aforementioned lithium transition metal oxide is lithium cobalt oxide. The positive electrode for a lithium-ion secondary battery according to feature 1.
5. The average particle size of the lithium transition metal oxide is 5 μm or more and 10 μm or less. The positive electrode for a lithium-ion secondary battery according to feature 1.
6. A positive electrode for a lithium-ion secondary battery according to any one of claims 1 to 5, A negative electrode capable of absorbing / releasing lithium ions, Non-aqueous electrolyte, A lithium-ion secondary battery characterized by having the following features.
Citation Information
Patent Citations
Positive electrode active material, and lithium ion secondary battery
JP2015103331A